Climate change awareness (knowledge and perception): Comparative study between natural science and social science students - Harahap, Yulia Fitri; Tyas, Intan Lestari Mulyaning; Sazaliana, Ade (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Climate change represents a critical and pressing global challenge that demands immediate attention. To effectively mitigate the impacts of climate change, it is essential to implement comprehensive educational programs that raise awareness, foster understanding, and equip individuals and communities with the knowledge and skills necessary to combat its effects. Climate change has been integrated into the curriculum in Indonesia across natural science and social science subjects. It is important to analyze the differences between these two subjects on climate change knowledge and perception. This study aims to compare students' knowledge and perceptions of climate change in natural science and social science students due to a gap in subject content. Furthermore, this study also examines the extent to which the level of knowledge affects students' perceptions of climate change. A questionnaire as a survey method about students’ knowledge and perceptions of climate change and its impacts was given to 150 students of natural science and social science students in MAN 2 Padang Sidempuan. The results indicated there is no statistically significant difference between natural and social students in terms of climate change knowledge and perceptions (sig. > 0.05). These findings imply that the distribution of climate change knowledge and perceptions is relatively uniform across disciplinary backgrounds.